Increased fatigue endurance in Pb(Zr,Ti)O3 thin films through use of PbZrO3 buffer layers - Alkoy, EM; Alkoy, S; Uchiyama, K; Shiosaki, T (Inst Pure Applied Physics, 2006)
Thin PbZrO3 (PZ) films were investigated as a buffer layer to improve fatigue endurance of Pb(Zr0.45Ti0.55)O-3 (PZT) thin films. The PZ thin films were deposited on Pt-(III)/Ti/SiO2/Si-(100) substrates by RF magnetron sputtering from a loose powder target containing a mixture of PbZrO3 and ZrO2 powders. The PZT thin films on the PZ buffer layer were obtained by sol-gel spin coating. The PZ buffered PZT films had well crystallized, uniform and dense microstructure with partial (111) orientation. The P-E hysteresis measurements indicated comparable or slightly lower remnant polarization values (2P(r) = 50 - 70 mu C/cm(2)) and higher coercive field levels compared to unbuffered film (2P(r) = 66 mu C/cm(2)). The PZ buffered films displayed an asymmetric leakage current. The fatigue endurance of PZT thin films with PZ buffer layers was superior compared to the unbuffered counterpart with fatigue-free behavior observed up to 109 switching cycles.
Keywords: lead zirconate titanate; thin films; fatigue; buffer layers